Kształtowanie przekazu marketingowego i wizerunku produktu na przykładzie wybranego asortymentu słodyczy eksportowanych z polski - Socha, Dominika (Shaping the Marketing Message and Image of The Product Exemplified by Selected Assortment of Sweets Exported from Poland, 2008)
Recent years saw systematic growth of Polish confectionery export, with approximated 540 million EUR income in the year 2006. This type of products is sold mainly to EU countries, Russian Federation and Eastern/Central Europe. For such expansion of export markets to be effective and cooperative, managers in the field must show good knowledge of foreign languages, often on the proficiency level. Apart from better understanding of particular target markets, this allows for winning long-term partners as well as development of professional and clear marketing message with the adequate image of particular products on offer. Preliminary research of Polish confectionery companies shows that the most comprehensive knowledge of foreign languages prevails among employees of Polish branches of international companies, while SMB companies targeting single foreign market or area manifest the most limited linguistic competence. One common feature of employees working for foreign trade institutions is the tendency for self-learning and gaining linguistic competence through individualized training courses.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 81-87